Effects of temperature and humidity on high-strength p-aramid fibers used in body armor. Issue 21 (November 2020) - Engelbrecht-Wiggans, A; Burni, F; Guigues, E; Jiang, S; Huynh, TQ; Tsinas, Z; Jacobs, D; Forster, AL
To improve the reliability and design of body armor, it is imperative to understand the failure modes and the degradation rates of the materials used in armor. Despite the best efforts of manufacturers, some vulnerability of armor materials to aging due to hydrolytic or oxidative environments is expected and may result in the degradation of material properties such as tensile strength. In this work, p- aramid yarns from two manufacturers were exposed to environmental conditions of various fixed temperature and humidity combinations. The maximum temperature and humidity condition was 70℃ and 76% relative humidity (RH). Tensile tests were performed on specimens extracted at several different times over the course of at least 1 year to determine the change in ultimate tensile strength and failure strain as a function of time, temperature, and humidity. Molecular spectroscopy was used to investigate any chemical changes as a result of the aging. The p -aramid materials were found to be generally resistant to degradation at most conditions, showing changes of less than 10% only at the highest temperature and humidity conditions.